2019
DOI: 10.1111/imj.14182
|View full text |Cite
|
Sign up to set email alerts
|

Management of frail older people with acute illness

Abstract: Frailty status is intrinsically related to every aspect of older patients’ hospital journeys: the way in which they present to hospital, their health status at admission, vulnerability to complications in hospital and rate of recovery after an acute insult. In younger people, hospitalisation is usually the result of a serious illness or injury, such as sepsis or major trauma. Management can be underpinned by evidence‐based algorithms relating to the precipitating insult and recovery usually follows a predictab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Clearly, the admission of patients must be indicated based on economic factors as well as on aspects of the patient’s will and ethical considerations for elderly patients, who might experience massive stress due to the changed environment in the hospital [34]. A relevant but unanswered question underlying this study is, how does the fear of legal consequences affect clinical management, although a potentially fatal DIH may not lead to an escalation of care due to advanced patient age?…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the admission of patients must be indicated based on economic factors as well as on aspects of the patient’s will and ethical considerations for elderly patients, who might experience massive stress due to the changed environment in the hospital [34]. A relevant but unanswered question underlying this study is, how does the fear of legal consequences affect clinical management, although a potentially fatal DIH may not lead to an escalation of care due to advanced patient age?…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence that frailty is a significant predictor of hospitalisation and adverse outcomes after discharge in older people, such as readmission rates as well as increased risks of disability and mortality [1,14]. A prospective study implementing frailty screening and frailty pathway intervention among geriatric trauma and emergency general surgery patients in an acute hospital showed improvement of patients' outcomes including the reduction in length of stay, readmission rate, and loss of independence [15].Studies suggested frailty screening in hospital might benefit the patients by risk stratification and providing individualized and optimized care [16,17]. Hospitals have been increasingly stretched to cope with the influx of frail older patients and changes are needed to be made to address the shortage of beds in the acute hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…With an ageing population (Mudge & Hubbard, 2019), the healthcare system is faced with an increasing number of patients with chronic and complex health conditions. These adults have more frequent hospitalisations and re-admissions (Gallagher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%